Applications of the Voltammetry - Stoytcheva, Margarita; Zlatev, Roumen (IntechOpen, 2017)
The present book Applications of Voltammetry is a collection of six chapters, organized in two sections. The first book section is dedicated to the application of mathematical methods, such as multivariate calibration coupled with voltammetric data and numeric simulation to solve quantitative electroanalytical problems. The second book section is devoted to the electron transfer kinetic studies and electroanalytical applications of the voltammetry, such as interfacial electron transfer of the haem group in human haemoglobin molecules, physisorbed on glass-/tin-doped indium oxide substrates, analysis of dyes and metal ions in trace concentrations and characterization of the antioxidant properties of wine and wine products, using a variety of voltammetric techniques and electrodes. The most recent trends and advances in voltammetry are professionally commented.